ANALISIS KUALITAS PRODUK KONVEKSI BERUPA SERAGAM SEKOLAH DENGAN MENGGUNAKAN METODE SIX SIGMA DI TEMPAT PRAKTIK KETERAMPILAN USAHA (TPKU) BIDANG KONVEKSI TEBUIRENG - Ahmad Al Amin, Sumarsono, Nur Kholis (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
The rapid rate of growth of technology and information in the modern era today, encourages companies to further develop their thoughts and views to maximize the goals and objectives set. The Place to Practice Business Skills (TPKU), is a business engaged in the field of convection managed by Tebuireng Boarding School. One of the most widely used convection products is the school uniform. In producing school uniforms, convection also strives to continuously improve quality by pressing the number of defects in the product. Some things that need to be done are identifying the factors that cause disability using the Six Sigma method, calculate the quality of sigma, and propose appropriate actions to control the quality of school uniforms. Six sigma is a tool of quality improvement toward the 3,4 target of failure per a million opportunities for each production. So six sigma is one of the new methods in the field of quality management aimed at quality control and improvement. By using the six sigma method, it can be seen that there are seven types of defects (CTQ) that occur in school uniform products. The two most common types of defects are: seams that are not tidy with a percentage of 51.1% and stain on uniform of 28.4%. For the quality of school uniforms produced by Tebuireng Convection is still low ie 2.95 sigma with a product defect rate as much 74830 products in one million products (DPMO). From the application of these six sigma, it can be concluded that the proposed action to be done convection to reduce the level of product defects is to focus its supervision on improving employee performance, engine performance, applicable work standards, existing facilities and infrastructure, provide motivation to work, and improve time management well.